Posttranscriptional regulation of colonic epithelial repair by RNA binding protein IMP1/IGF2BP1. (6th May 2019) - Chatterji, Priya; Williams, Patrick A; Whelan, Kelly A; Samper, Fernando C; Andres, Sarah F; Simon, Lauren A; Parham, Louis R; Mizuno, Rei; Lundsmith, Emma T; Lee, David SM; Liang, Shun; Wijeratne, HR Sagara; et al.
Abstract: RNA binding proteins, including IMP1/IGF2BP1, are essential regulators of intestinal development and cancer. Imp1 hypomorphic mice exhibit gastrointestinal growth defects, yet the specific role for IMP1 in colon epithelial repair is unclear. Our prior work revealed that intestinal epithelial cell‐specific Imp1 deletion ( Imp1 Δ IEC ) was associated with better regeneration in mice after irradiation. Here, we report increased IMP1 expression in adult patients with Crohn's disease and ulcerative colitis.† We demonstrate that Imp1 Δ IEC mice exhibit enhanced recovery following dextran sodium sulfate (DSS)‐mediated colonic injury. Imp1 Δ IEC mice exhibit Paneth cell granule changes, increased autophagy flux, and upregulation of Atg5. In silico and biochemical analyses revealed direct binding of IMP1 to MAP1LC3B, ATG3, and ATG5 transcripts. Genetic deletion of essential autophagy gene Atg7 in Imp1 Δ IEC mice revealed increased sensitivity of double‐mutant mice to colonic injury compared to control or Atg7 single mutant mice, suggesting a compensatory relationship between Imp1 and the autophagy pathway. The present study defines a novel interplay between IMP1 and autophagy, where IMP1 may be transiently induced during damage to modulate colonic epithelial cell responses to damage. Synopsis: The RNA binding protein IGF2BP1/IMP1 is upregulated in patients with Crohn's disease and ulcerative colitis. Imp1 deletion increases autophagy and recovery from colonic epithelial damage, suggesting that IMP1 modulates colonic inflammation and epithelial homeostasis. Mice with Imp1 deletion exhibit increased autophagy flux and enhanced recovery from colonic epithelial damage. IMP1 protein binds directly to autophagy transcripts. Deletion of autophagy gene Atg7 sensitizes mice with Imp1 deletion to colonic epithelial damage. Abstract : The RNA binding protein IGF2BP1/IMP1 is upregulated in patients with Crohn's disease and ulcerative colitis. Imp1 deletion increases autophagy and recovery from colonic epithelial damage, suggesting that IMP1 modulates colonic inflammation and epithelial homeostasis.